Avaliação dos parâmetros hematológicos e imunofenotípicos de pacientes com doenças linfoproliferativas crônicas no Rio Grande do Norte - Paiva, Aldair de Sousa (2014)
Chronic lymphoproliferative disorders (DLPC) are lymphoid system diseases characterized by the abnormal proliferation of mature lymphocytes that affect B cells, T lymphocytes and NK cells. The aim of the study was to demonstrate the relevance of immunophenotyping by flow cytometry in patients with prolonged lymphocytosis and / or cytomorphological changes compatible with lymphoproliferative diseases. In this study 460 patients (244 men and 216 women) with DLPC were evaluated. Were analyzed by flow cytometry with a panel of monoclonal antibodies consisting of CD3, CD4, CD5, CD8, CD10, CD19, CD22, CD23, CD25, CD38, CD45, CD16/CD56, and HLADR heavy and light chains of immunoglobulins. It also examines information regarding age, gender of patients and laboratory data as leucocytes, cytomorphological analysis, platelet count and hemoglobin determination. The results showed 398 cases of chronic lymphoproliferative disorders and 62 of DLPC B cell lymphoproliferative diseases T. B showed the following distribution : 253 cases of chronic lymphocytic leukemia (CLL), 42 cases of multiple myeloma ( MM ), 37 cases of lymphoma non - Hodgkin lymphoma in leukemic phase (NHL) , 17 cases of pro- B lymphocytic leukemia ( B -PLL), 15 cases of mantle cell lymphoma (MCL ), 12 cases of plasma cell leukemia ( PCL), 9 cases of lymphoma Burkitt (Linf B), 8 cases of leukemia villous cells ( LCV), 3 cases of splenic lymphoma with villous cells (LECV), a case of follicular lymphoma (LF) and a Waldenströn macroglobulinemia ( MW). The diseases source NK / T were 23 cases of peripheral T cell lymphoma (LCTP), 14 cases of T prolymphocytic leukemia (T -PLL), 10 cases of leukemia T of large granular lymphocytes (LGL -T) 9 cases of leukemia cells of adult T (LCTA), 5 cases of Sezary syndrome (SS) and a case of large granular NK leukemia (LGL -NK) lymphocytes. In conclusion, the combined use of the monoclonal antibody panel careful cytomorphological analysis was shown to be essential in immune diagnosis and classification of chronic lymphoproliferative disorders. This study was approved by the IRB - HUOL under number 356 / 09